How do biochar size fractions and organic fertilizers interactively influence nitrous oxide emission from a tropical vertisol?. Issue 6 (27th September 2022) - Kollah, Bharati; Ahirwar, Usha; Parmar, Rakesh; Devi, Mayanglambam Homeshwari; Atoliya, Nagvanti; Shinoji, K. C.; Patra, Ashok; Singh, Amar Bahadur; Dubey, Garima; Mohanty, Santosh Ranjan
Abstract: Background: Nitrous oxide (N2 O) emission from agriculture is increasing alarmingly due to intensive application of inorganic and organic fertilizers. Recently, biochar has been identified as a promising additive to improve agriculture by enhancing soil function and mitigate greenhouse gas emission. However, it is unclear how biochar of different size fractions influences N2 O emission from agricultural soil. Aims: The current experiment aims to understand how the size of biochar (BC) and organic fertilizers interactively influence N2 O emission from a tropical vertisol. Methods: BC was prepared using pigeon pea ( Cajanus cajan ) stalks and further processed to obtain two size fractions (<0.25 mm or 0.25–2.00 mm). Organic fertilizers (vermicompost [VC], poultry manure [PM], or farmyard manure [FYM]) and BC were added to soil to evaluate N2 O emission potential. BC was added to soil at 10% (w/w), whereas the organic fertilizers were added at 80 kg N ha –1 . Emission of CO2 and the abundance of 16S rRNA and amoA gene copies were estimated after incubation period. The interactive effect of BC size fractions and organic fertilizers were statistically evaluated. Results: Both BC and organic fertilizers stimulated N2 O emission in soil. BC of larger size stimulated N2 O emission (µg N2 O produced g –1 soil day –1 ) more than smaller size. Of the three organic fertilizers, PM resulted highest N2 O (0.380) emission followed by FYM (0.240) and VC (0.210). BC (0.25 mm) + PM produced least N2 O. Abundance of heterotrophic bacterial 16S rRNA gene copies and ammonia‐oxidizing bacterial (AOB) amoA gene copies were highest in PM + BC and lowest in control. Significant relation ( p < 0.0001) existed among N2 O emission, CO2 emission, and microbial abundance. Conclusions: BC of small size fraction along with organic fertilizers can be an effective strategy to mitigate N2 O emission from tropical vertisol.